DIETARY SUPPLEMENTS IN THE MANAGEMENT OF HYPERTENSION AND DIABETES - A REVIEW - Afolayan, Anthony Jide; Wintola, Olubunmi Abosede (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: The use of alternative therapies like herbs and dietary supplements is very common among hypertensive and diabetic patients all over the globe. Hypertension is a silent disease that causes increase in cardiovascular, cerebrovascular, renal morbidity and mortality whereas diabetic complications cause heart attack, stroke, blindness and kidney disease. These are serious and chronic metabolic disorders that have a significant impact on the health, quality of life, and life expectancy of patients, as well as on the health care systems. Orthodox drugs used for the treatment of hypertension and diabetes produce side effects such as headache, nausea, vomiting, stomach pain, constipation, diarrhea, weakness, fatigue and erectile dysfunction. The need for considering alternate therapies in the form of dietary supplements known to promote good health, having little or no side effects therefore arises. Materials and methods: This review was carried out using comprehensive and systematic literature reports on the concurrent use of dietary supplements in the management of diabetes and hypertension. Empirical searches were conducted using Google scholar (http:// scholar. google.com), and Science Direct (http://www.science direct.com). In addition to these databases, the University database was also used. Searches were also undertaken using keyword combinations such as dietary supplements and the names of the diseases in question. Result and Discussion: This review chronicled the therapeutic values of vitamins, minerals, amino acids, fruits, vegetables, herbs and other botanicals used as dietary supplements. Results show that these supplements provided better and safe substitutes to toxic and expensive conventional drugs. Generally dietary supplements are free from major side effects, readily available and affordable. It is envisaged that the use of dietary supplement will promote good health and improve the status of hypertensive and diabetic patients. Conclusion: Medical doctors are therefore encouraged to incorporate dietary supplements into the regimen employed for hypertension and diabetes management.